Deutsch-slavische Literaturbeziehungen im 18. Jahrhundert - Drews, Peter (Slavistische Beitraege, 1996)
The present study would like to close at least some of the previous gaps in a concise overview, which is why also previously overlooked seemingly marginal areas of the literature of the belles lettres and the hymn. It confines itself to the presentation of the direct journalistic effects of the literature exchange in the form of translations and literary criticism, thus for example dispensing with the inclusion of correspondence already printed in part anyway.